PENGARUH PROFITABILITAS, SOLVABILITAS, UKURAN PERUSAHAAN DAN OPINI AUDIT GOING CONCERN TAHUN SEBELUMNYA TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MINYAK, GAS DAN BATU BARA YANG TERDAFTAR DI BEI 2019-2022 - Putri, Seppi Suciani; Oemar, Fahmi; Salmiah, Neneng (Komunitas Manajemen Kompetitif, 2024)
The purpose of this study is to determine how factors such as profitability, creditworthiness, company size, and the prior year's business continuity assessment report affect the current business continuity assessment report. The methodology of this study was quantitative. The study examined ten oil, gas and coal companies listed on the Indonesian Stock Exchange between 2019 and 2022. The study used a deliberate sampling technique to determine the sample size. Using SPSS version 25, this study used logistic regression analyzes to test the hypothesis. The audit results showed that the size, profitability and creditworthiness of the company have a significant impact on the audit opinion on the going concern. The going concern statement for the current year had no impact on the going concern statement for the previous year. Keywords: Profitability, solvency, company size and business continuity compared to the previous year. audit opinion